Improved of Sliding Mode Control for Maximum Power Point Tracking in Solar Photovoltaic Applications Under Varying Conditions - Hassan, Alaq F.; Nawfal, Mohanad; Al-Khazraji, Huthaifa; Humaidi, Amjad J. (International Journal of Robotics and Control Systems, 2025)
The solar energy generation sector has received widespread interest compared to other types of sustainable energy generation. This is owing to its high efficiency and the availability of environmental factors essential to the operation of these systems in various parts of the world. However, increased the power extracted from these systems are a critical issue as their conversion efficiency is low. Therefore, a maximum power point tracking (MPPT) controller is necessary in a photovoltaic generation system (PV) for maximum power extraction. This study aims to explore the performance of the MPPT system that uses an improved sliding mode controller (SMC) to identify and track a maximum power point (MPP) of a PV system and compares it to synergetic algorithm control (SACT). To implementing this purpose, MATLAB/Simulink model of a stand-alone PV panel is developed. Then, the analysis of the performance efficiency of the PV system based on the proposed MPPT methods are implemented under varying environmental conditions. Being able to track the MPP perfectly in the case of a sudden change in environment conditions, the improved SMC is proven by the results to be superior in stabilizing the boost converter's operation, leading to enhanced PV system stability. This has led to a reduction in power losses and an increase in efficiency.